Tranexamic Acid Use in United States Trauma Centers: A National Survey. Issue 5 (May 2016) - Jawa, Randeep S.; Singer, Adam; Mccormack, Jane E.; Huang, Emily C.; Rutigliano, Daniel N.; Vosswinkel, James A.
Tranexamic acid (TXA) is an antifibrinolytic agent that is listed as an essential medication by the World Health Organization for traumatic hemorrhage. We determined United States–based surgeons' familiarity with TXA and their use of TXA. An online survey was sent to the 1291 attending surgeon members of a national trauma organization. The survey was organized into three general parts: respondent demographics, perceptions of TXA, and experience with TXA. The survey was completed by 35 per cent of members. TXA was available at 89.1 per cent of centers. Experience with TXA was variable: 38.0 per cent use regularly, 24.9 per cent use it 1 to 2 times per year, 12.3 per cent use it rarely, and 24.7 per cent had never used it. Among surgeons who had used TXA, 77.1 per cent noted that TXA had reduced bleeding, but 22.9 per cent indicated that it had not. Reasons for not routinely using TXA included uncertain clinical benefit (47.7%) and unfamiliarity (31.5%). Finally, 90.5 per cent of respondents indicated that are looking toward national organizations to develop practice guidelines. TXA is widely available in civilian United States trauma centers. Although a majority of surveyed surgeons had used TXA, only 38 per cent use TXA regularly for significant traumatic hemorrhage; principal reasons for this are uncertainty regarding clinical benefit and unfamiliarity with the drug. National guidelines are sought.